The Synergy of Muslim Communities Abroad in Preventing Islamic Radicalism (Evidence from Indonesia Muslim Community in Victoria, Australia) - Ahmad Dahlan; Akhmad Faozan (Ijtimā iyya Journal of Muslim Society Research, 2021)
IMCV (Indonesian Muslim Community in Victoria) was founded in 1997. Its existence and activities have been widely published in print and online media. However, these publications have yet to present IMCV as an organization that synergizes in counteracting radical Islamic ideology. The existence of IMCV is very strategic because its members are comprehensive and supported by several militant organizations, namely the young Indonesian generation in Australia, such as YIMSA (Young Islamic Muslim Students Association). This article found evidence of the synergy of IMCV as an Islamic organization of Indonesians in the state of Victoria will describe the synergy of IMCV in winning over Islamic radical ideas.